2016
DOI: 10.1097/mbp.0000000000000171
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in white coat and sustained hypertension

Abstract: Our data show that sustained hypertensive patients have lower vitamin D levels than white coat hypertensive and normotensive individuals. White coat hypertensive patients without other cardiovascular risk factors have higher vitamin D levels than sustained hypertensive patients, suggesting that they have a lower cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Many authors have stated that a decrease in vitamin D levels increases the risk of HT [ 1 2 ]. However, results of studies that investigated the relationship between vitamin D levels and BP in HT patients are conflicting [ 8 11 ]. Some studies have reported higher levels of vitamin D in HT patients as compared with NT subjects [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many authors have stated that a decrease in vitamin D levels increases the risk of HT [ 1 2 ]. However, results of studies that investigated the relationship between vitamin D levels and BP in HT patients are conflicting [ 8 11 ]. Some studies have reported higher levels of vitamin D in HT patients as compared with NT subjects [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, results of studies that investigated the relationship between vitamin D levels and BP in HT patients are conflicting [ 8 11 ]. Some studies have reported higher levels of vitamin D in HT patients as compared with NT subjects [ 8 , 9 ]. In these studies, an inverse association between vitamin D levels and BP was found [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations